The Use of Palm Oil as New Alternative Biolubricant for Improving Anti-Friction and Anti-Wear Properties - Norzahir, Sapawe; Muhammad Farhan, Hanafi; Syahrullail, Samion (Elsevier Ltd., 2019)
Metal-on-metal (MoM) hip replacements are commonly used hip implants. However, one of the issues under debate is the interference of friction and wear. The purpose of this feasibility study is to elucidate the performance of palm lubrication between the femoral head and the acetabular cup. In the tribology of hip implants, the use of palm oil as natural lubricants for human joints has shown tremendous potential. Palm oil give significant value as alternative biolubricant due to its advantages, large production in country, and also has potential to replace petroleum based lubricants. A modified pin-on-disc as hip screening has been used to evaluate the friction and wear on an acetabular cup. The wear debris was then observed with microscopy image analysis. This study revealed that the physical and unique chemical properties in palm oil can optimize the rate of friction and wear on the metal acetabular cup and thus allow for a stable implant of MoM.